Percutaneous transluminal coronary angioplasty in patients with spasm superimposed on atherosclerotic narrowing. - Bertrand, M E (1987)
Of 552 patients undergoing percutaneous transluminal coronary angioplasty 102 had coronary artery spasm superimposed on atherosclerotic narrowing. Coronary angioplasty was successful in 97 (95%). The patients were discharged on a regimen of nifedipine (40-60 mg/day). Seventy six patients were symptom free 6-8 months after the procedure. Restenosis was detected in 35% of patients. Coronary artery spasm was provoked in 38 (44%) of the 87 patients who underwent an ergometrine maleate test. Twenty seven of the 34 patients with restenosis had a provocation test and coronary artery spasm was superimposed on restenosis in 22 (81.5%). Coronary angioplasty is feasible in patients with coronary artery spasm superimposed on atherosclerotic narrowing but the rate of restenosis is high and coronary artery spasm could have a role in the pathogenesis of restenosis.